Analisis Penerapan Akuntansi Biaya Lingkungan pada Industri Pabrik Tahu Super Jaya - Christianus Tomy Saputra; Wilhelmina Mitan; Pipiet Niken Aurelia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the application of environmental cost accounting in the Super Jaya tofu factory industry. This research uses qualitative methods. In this research, the data sources used are primary data and secondary data. The data collection technique uses observation, interviews and documentation. By conducting direct interviews with the owners of the Super Jaya tofu factory industry. The data analysis technique uses data collection, data reduction, data presentation, conclusions and data verification. The research results obtained from the application of environmental cost accounting are still not effective because they have not prepared financial reports and have not implemented cost accounting in presenting financial reports because the costs traced are only general costs related to the tofu production process. Such as raw material costs, labor costs, general capital costs and special capital costs, while the costs for waste management are only labor costs for the filtering section and environmental cleaning equipment costs.